2010
DOI: 10.1111/j.1475-1305.2009.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue on Shot‐Peened Gears: Experimentation, Simulation and Sensitivity Analyses

Abstract: The present paper deals with fatigue experimentation and with the application and improvement of predictive models; in addition, a sensitive analysis is performed on the main factors related to the shot‐peening treatment and on the efficiency of the aforementioned models. The research involved gears, made of high‐strength steel and carburised, quenched, ground, shot‐peened and superfinished. The experimental campaign initially dealt with the investigation into the influence of isotropic superfinishing; the att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…At the same time, it should be noticed that the used approach did not take the high residual stress field formed by the UIT process and/or other surface thermo-mechanical treatments into explicit consideration. It was recently suggested that the whole stress distribution within surface layer should be taken into account for the fatigue prediction of the shot-peened components containing high residual stresses, and the role of mean stress for this method must be treated by running an iteration procedure [58].…”
Section: Fatigue Limit and Critical Cracksmentioning
confidence: 99%
“…At the same time, it should be noticed that the used approach did not take the high residual stress field formed by the UIT process and/or other surface thermo-mechanical treatments into explicit consideration. It was recently suggested that the whole stress distribution within surface layer should be taken into account for the fatigue prediction of the shot-peened components containing high residual stresses, and the role of mean stress for this method must be treated by running an iteration procedure [58].…”
Section: Fatigue Limit and Critical Cracksmentioning
confidence: 99%
“…4-6) deviates from the classical distribution found for shot peening which often display subsurface compressive stress peak [11,13,14]. Other shapes of residual stress curves, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…with a surface stress plateau, were also found in the literature but less common. Some of the non-classical stress distributions could be related to multi-peening [14,15] or peening induced phase transformation [4]. Measurements on steels of different yield strengths [16] showed that the strength of the target material can also be important.…”
Section: Resultsmentioning
confidence: 99%
“…Bagherifard et al [11] tried to predict the fatigue resistance of peened notched parts measuring RSs far from the notch, thus neglecting the perturbation exerted by the notch on the RS field in terms of intensity and mono-or multi-axiality. Laboratory XRD measurements were taken on the root of peened notches [24][25][26][27][28], but the millimeter size of the irradiated area impeded to resolve the lateral gradient of the RS distribution. King et al [29] used energy dispersive synchrotron XRD to measure inplain residual strains at the root of the notch of shot peened samples.…”
Section: Introductionmentioning
confidence: 99%